Implementasi Stimulus Respon Behaviorisme Melalui Terapi wicara Pada Gangguan Fonologis Berbahasa Anak Tunagrahita di Panti Asuhan Yatim Sejahtera Banjarnegara - Nurharyani, Octaria Putri; Prasetyo Nugroho, Bivit Anggoro; Marahayu, Nila Mega (PEMBELAJAR: Jurnal Ilmu Pendidikan, Keguruan, dan Pembelajaran, 2024)
Stimulus Response Behaviorism is one of the approaches used to promote speech therapy for cognitively impaired children. The purpose of this study was to describe the relationship between Stimulus-Response Behaviorism and speech therapy for a 5.5-year-old cognitively impaired child at the Yatim Sejahtera Banjarnegara Orphanage. The data source of this research is a 5.5-year-old cognitively impaired child and the data of this research is the vocabulary of cognitively impaired child who has language disorders, especially in her phonetic pronunciation. Furthermore, a cognitively impaired child received stimulus response behaviorism assistance in speech therapy to improve pronunciation and vocabulary after being given stimulus response and reinforcement in providing speech therapy actions. The vocabulary produced has noun and adjective categories on vocabulary cards consisting of names of colors, fruits, and foods. Qualitative descriptive method was used in this study. Data was obtained in the form of vocabulary that had improved significantly after being treated with stimulus-response behaviorism. Using the vocabulary obtained, it is analyzed further to find out how the stages of language phonology development in cognitively impaired child are through the phonetic syllabization stage. The results of this study indicate that stimulus response behaviorism theory has a significant impact on the implementation of speech therapy as seen in the pronunciation of the phonological vocabulary of a cognitively impaired child who has a language disorder.